Presentation - Quirós-Arias, Lilliam (2021)
The REVISTA GEOGRÁFICA DE AMÉRICA CENTRAL (translated as GEOGRAPHICAL JOURNAL OF CENTRAL AMERICA) is a publication of the School of Geographical Sciences of the Faculty of Earth and Sea Sciences at the Universidad Nacional (UNA), Costa Rica, published periodically by the Publishing Office of the Universidad Nacional (Editorial Universidad Nacional, EUNA) since 1974. The Journal is intended to disseminate research and works of relevance in geography and related sciences through the publication of original works, unpublished reports, or research advances that hold special relation to Central America, addressing specific topics of Geography: regional studies, urban/rural issues, land use planning, natural resources and their relationship with the geographic environment, watershed management, geographic information sciences, demographic analysis, epistemology related matters and the teaching of this discipline.  In addition, it constitutes a forum for the expression of professional opinion and academic discussion, and as such, it includes all scientific contributions to achieve this purpose. On this occasion, it corresponds to publication N°68 of the Revista Geográfica de América Central of the first semester of 2022 (January-June). It includes 15 articles distributed throughout the different sections of the Journal: theory, epistemology, methodology and case studies.